2019
DOI: 10.1007/s42452-019-1306-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of microbial air quality in preschools on paediatric respiratory health

Abstract: Microbial air quality (MAQ) is unambiguously linked with one's health particularly in pulmonology. Children remain more vulnerable in acquiring airborne infections than adults. MAQ studies and management are being implemented in developed countries, yet such information and actions are scarce in developing countries. Herein, we aimed to determine the indoor and outdoor airborne microbial concentrations in a rural versus urban perspective and their association with paediatric respiratory health. Preschools, one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Various studies have been conducted throughout the World to assess microbial concentration in other indoor sites such as schools, colleges, hospitals, and public libraries or; but less attention was paid to residential houses (Madhwal et al, 2020 ; Frankel et al, 2012 ; Kumari et al, 2016 ; Park et al, 2016 ; Madamarandawala et al, 2019 ; Karmakar et al, 2020 ). Few studies have been conducted in Delhi to assess the bioaerosols concentrations in indoor environments (Gupta et al, 1993 ; Sharma, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted throughout the World to assess microbial concentration in other indoor sites such as schools, colleges, hospitals, and public libraries or; but less attention was paid to residential houses (Madhwal et al, 2020 ; Frankel et al, 2012 ; Kumari et al, 2016 ; Park et al, 2016 ; Madamarandawala et al, 2019 ; Karmakar et al, 2020 ). Few studies have been conducted in Delhi to assess the bioaerosols concentrations in indoor environments (Gupta et al, 1993 ; Sharma, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bioaerosols are also capable of long range transport and hence, the microbial consortia observed in this event could be associated with the bioaerosols generated from the haze origin, but, the reality and to which percentage is yet unknown. As per literature, O. intermedium [11], B. megaterium, B. cereus and Exiguobacterium acetylicum [18] have been previously identified in the Kandy atmosphere; perhaps, the haze condition might have favored their survival. Certain bacteria are capable of tolerating harsh environmental conditions through mutations in their genetic makeup.…”
Section: Resultsmentioning
confidence: 80%
“…These pieces were suspended in sterile Milli-Q water and were shaken in an orbital shaker (ORBITEK, Scigenics Biotech, India) for 2 h. Following extraction of bacteria into Milli-Q water, extracts were centrifuged at 12,000 rpm for 5 min. The supernatants were discarded having 1 mL of sedimented bacteria remaining for further applications [18].…”
Section: Sampling Site Sample Collection and Processingmentioning
confidence: 99%
“…High indoor bacterial load and other physical features are responsible for the health problems in the students and staff in residential buildings (Andualem et al, 2019). A similar study conducted by (Madamarandawala et al, 2019) suggested that 58% of urban and 31% preschool students were suffering from at least one health effect related to the microbial air quality. Bezerra and co-workers evaluated the serum concentration in the children suffering from the allergic reactions, and levels were found to increased (Bezerra et al, 2016).…”
Section: Health Effects Of Microbial and Indoor Air Quality On Subjectsmentioning
confidence: 92%
“…Seasonal variation can be shown in the composition and abundance of AM indoor air furthermore, can be associated with the factors such as temperature, relative humidity, and air exchange rate (Frankel et al, 2012; Kumari et al, 2016;Park et al, 2016). The presence of AM in prenursery schools may also affect the respiratory and pediatric health and well-being of the children (Madamarandawala et al, 2019). Aspergillus, Curvularia, Penicillium, and Rhizopus were the main fungal genera record from the different indoor areas in Kolkata, India (Karmakar et al, 2020).…”
Section: Introductionmentioning
confidence: 98%